Extraction of essential oils from jasmine flower using solvent extraction method : A study on feed ratio effects - Thavaselvan, Superamaniam (2008)
Jasmine essential oils are primarily used in the perfumery industry and have a very high commercial value due to its therapeutic properties. As Jasmine essential oils are composed of heat-sensitive chemical compounds,the use of conventional steam distillation technique would inevitably inflict thermal degradation to the natural fragrance. In this experimental work, solvent extraction method was employed due to its mild extracting condition and lower operating cost. Ethanol was used as the solvent due to its high availability in market. The extract compositions were compared using gas chromatography analysis. Preliminary results showed that volatile oil compounds were successfully isolated from Jasmine flowers using these solvents. It was found that the main constituents of the essential oils were benzyl acetate and benzyldehyde. Further studies also revealed that the composition and yield of essential oils influenced by the ratio of ethanol solvent to the jasmine flower.The most optimum feed ratio of jasmine flower to ethanol solvent is 1: 2 (50mg:100mL) where it’s yield is 14.65% and having process efficiency of 19%. Low yield of the jasmine essential oils can be improved by varying this ratio and carrying out the research in larger scale.